The bacterial diversity and potential pathogenic risks of giant panda-infesting ticks - Rui Ma; Yi Shi; Wei Wu; Chong Huang; Fei Xue; Rong Hou; Yanshan Zhou; Jiang Gu; Feifei Feng; Xiang Yu; Jiabin Liu; Zusheng Li; et al. (Microbiology Spectrum, 2025)
ABSTRACT As common parasites in the wild, ticks significantly limit the population growth of wild giant pandas and hinder the process of reintroducing captive giant pandas into their natural habitats. Research on microbial communities and pathogens in ticks infesting giant pandas is limited, emphasizing the need for a comprehensive investigation. To thoroughly investigate the microbial communities in giant panda-infesting ticks, particularly potential pathogens, we analyzed 246 ticks collected from the ears of wild-living giant pandas using 16S rRNA and metagenomic sequencing. We found that the microbial diversity in female ticks was significantly enriched in summer. The microbial community structure carried by ticks is more significantly influenced by seasonal changes than by sex. Metagenomic results indicated that giant pandas have a higher risk of Coxiella burnetii infection in summer and a higher risk of Anaplasma phagocytophilum, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Rickettsia amblyommatis infections in autumn. Over 90% of the ticks carried pathogens, with 82.54% harboring a single potentially pathogenic symbiont and the remaining 17.46% carrying multiple pathogens, all involving Coxiella burnetii. Using the CARD database, we identified a total of 121 antibiotic resistance genes (ARGs), with 76% exhibiting antibiotic efflux mechanisms. Based on the significantly associated ARGs, we provided antibiotic treatment recommendations for infections potentially caused by pathogenic symbionts. This study provides a clear answer to the potential microbial pathogen risks of ticks infesting giant pandas and offers a framework for tick-borne diseases in reintroduced wild panda populations.IMPORTANCEImportance: The emergence of tick-borne bacterial diseases poses a serious threat to the population health of wild-living giant pandas. Ticks are obligate hematophagous ectoparasites that survive by feeding on the blood of various animal hosts and spreading pathogens. Although some previous studies have confirmed that wild ticks carried various viruses, the role of wild giant panda-infesting ticks in the bacterial community remains unknown. Here, the identification of the microbial community and antibiotic resistome in giant panda-infesting ticks revealed that most Ixodes ovatus ticks are potentially pathogenic symbionts, including Anaplasma phagocytophilum, Coxiella burnetii, and Rickettsia amblyommatis. Tick-borne disease control also needs to take into account the effects of season, sex, and antibiotic efflux resistance genes. Our findings highlight the contribution of the scientific management of tick-borne diseases in the giant panda population.